Think Outside the Box and Move Beyond the Market Share - Hafeez, Shakir; Munaf, Kinza; Zahid, Komal; Tariq, Madiha; Shabbir, Shaza; Khan, Sana (International Review of Management and Marketing, 2016)
This research paper contributes to the newly emerged area of research that has shifted the focus of the marketers and concerned stakeholders from the conventional evaluation and assessment of measuring a company’s true success; that is from market share to share of heart and share of mind. A qualitative focused group approach was applied to the study by taking two industries: black tea and cellular telecommunication services. A total of 73 subjects were taken. Among which some were tea drinkers and some were cell phone users. It was found that the brands that had high market share did not usually have high heart share and mind share. Having a larger market share does not necessarily mean being successful in its true sense and meaning. People might just be using a brand simply because they don’t have a choice. To be a winning brand with having success on all its facets and areas the marketers and concerned parties should not only focus on increasing the number of users but also focus on capturing more mind share and heart share as only then they can truly have an iconic brand. Keywords: Mind share; Heart share; Brand associations; Brand perceptions JEL Classifications: M14, M3